Composite Power System Reliability Evaluation Based on Efficient State Search Using Binary Grasshopper Optimisation Algorithm - Jayanthi, K; Bakkiyaraj, R. Ashok (International Journal of Computer Sciences and Engineering, 2025)
Reliability is a vital aspect for the safe operation of any modern technological system. This work presents a methodology for evaluating the reliability of a composite power system with Binary Grasshopper Optimisation (BGHO) algorithm in its search mechanism to select the dominant states of the system which have large existing probability and higher load curtailment. A Grasshopper of a BGHO algorithm represents the possible system state. BGHO is used for efficient exploration of system states in the problem space by generating different potential solution to achieve optimal objective. The examined system states are used to evaluate annualized system and load point reliability indices. The proposed search methodology is applied to IEEE-RTS test system and the results are compared with state of art approaches. This proposed methodology evaluates the indices similar to the existing benchmark methods while visiting less number of system states